Membaca Gerakan dan Ideologi Salafi di Indonesia - Ahmadi, Ahmadi; Usman, Jamiludin (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2022)
In recent years, there have been many debates among Muslims, especially among the Muslim scholar community regarding the use and understanding of the meaning of the Salaf in general, some claim (justify) that Salafus-Saleh is the basis of the way of religion, but if you look at it historically (historically) so there is a deep and sharp difference between the 19th century thinkers (reformist thinkers) and the early 20th century, for example between Jamalud Din al-Afghani (1838-1989) and Muhammad Abduh (1849-1905) who was known for the Salafiyah movement. , then in the next era appeared intellectuals (radical activists) such as Sayyid Qutb who was associated with the term neo-Salafi (Islamism, the term used by Oliver Roy. Throughout history, Muslims have continued to run, thoughts and understandings have continued to develop, thus having an impact on differences in expression and form. salafi, but as time goes by, the phases that experience differences are on the basis of The Salafi movement and ideology is a renewal and reform movement.